Synthesis, Characterization And Biological Properties Of Nickel- And Iron- Carboxylate Complexes - Ch'ng , Cynn Dee (2010)
In this research, nine Ni(II) complexes were successfully synthesized using nickel(II) chloride hexahydrate, NiCl2.6H2O with amino acids (Glycine, β-alanine and Lhistidine), carboxylic acids (2-picolinic acid, 3,5-dinitrobenzoic acid, 4- aminobenzoic acid and pyrazine-2-carboxylic acid) and with dicarboxylic acids (maleic acid and pyridine-2,6-dicarboxylic acid). Besides, two Fe(II) complexes and one Fe(III) complexes were also successfully synthesized. Fe(II) complexes were synthesized using iron(II) chloride 4-hydrate, FeCl2.4H2O with pyrazine-2- carboxylic acid and maleic acid respectively.